É possível desenvolver a autorreflexão no estudante de primeiro ano que atua na comunidade? Um estudo preliminar - Prearo, Alice Yamashita [UNESP]; Monti, Fernanda Miranda Fumelli [UNESP]; Barragan, Elena (FapUNIFESP (SciELO), 2012)
In a multiprofessional, discipline-based curriculum with cumulative and cognitive assessment, anew discipline based on University-Community Service Interaction (IUSC), for medicine and nursing students at a São Paulo school, aimed at finding a way to evaluate students’ development of communication and self-reflection skills. Overall assessment of students in small groups conducted through written reports and group portfolios failed to demonstrate self-reflection on the learning process in some students. A pilot study was therefore proposed, involving 15 students, divided into two randomly-selected groups, who agreed to develop an individual and reflective portfolio. Qualitative analysis of the material outlined categories such as reflection on student life before the chosen university course began, life experiences that led the student to the chosen career, correlation between learning the subject and professional practice and ability to identify their growth in communication skills, indicating an efficient process of self-reflection on their learning.

Numa faculdade com currículo tradicional e predomínio da avaliação cognitiva e somativa, uma nova disciplina, baseada na interação entre universidade, serviços e comunidade (Iusc), para estudantes de Medicina e Enfermagem numa escola de São Paulo, teve por objetivo buscar uma forma de avaliar o desenvolvimento do aluno em habilidades de comunicação e autorreflexão. A avaliação global do aluno em pequenos grupos feita por meio de relatórios escritos e portfólio do grupo não evidenciou a autorreflexão sobre o processo de aprendizagem de alguns estudantes. Foi proposto, então, um estudo piloto com 15 alunos, divididos em dois grupos, selecionados aleatoriamente, que aceitaram desenvolver um portfólio individual e reflexivo. Na análise qualitativa do material, identificou-se a presença de categorias como reflexão sobre a vida estudantil antes do curso universitário escolhido, experiências de vida que levaram à escolha profissional, correlação do aprendizado na disciplina com a prática profissional e capacidade de identificar o crescimento em habilidades de comunicação, mostrando-se eficiente no processo de autorreflexão sobre a aprendizagem.
Is it possible for first year students working in the community to develop self-reflection? A preliminary study
Keywords: Education, medical; Education, nursing; Primary health care; Educational measurement; Educação médica; Educação em enfermagem; Atenção primária à saúde; Avaliação educacional